2016
DOI: 10.1016/j.bbrc.2016.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic insight into the effects of the Salmonella ubiquitin ligase SlrP on host cells

Abstract: The virulence of the human and animal pathogen Salmonella enterica serovar Typhimurium is dependent on two type III secretion systems. These systems translocate proteins called effectors into eukaryotic host cells. SlrP is a Salmonella type III secretion effector with ubiquitin ligase activity. Here, we used two complementary proteomic approaches, two-dimensional gel electrophoresis and iTRAQ (isobaric tags for relative and absolute quantification) to study the consequences of the presence of SlrP in human epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In addition, a mouse model (strain 129SvJ) to study the role of single effectors in persistence, the ability of bacteria to survive in the host weeks after infection, revealed that both SspH1 and SspH2 significantly contributed to persistence of S. enterica serovar Typhimurium during systemic infection [ 194 ]. Studies carried out at the cellular level suggested that heterologous expression of SlrP in human epithelial HeLa cells induced defects in migration and adhesion [ 195 ] and increased cell death [ 105 ]. Additionally, using HeLa cells as infection model, SspH1 was shown, together with SptP, to downregulate the NF-κB-dependent expression of the pro-inflammatory cytokine IL-8 [ 137 ].…”
Section: E3 Ubiquitin Ligases Of the Nel Familymentioning
confidence: 99%
“…In addition, a mouse model (strain 129SvJ) to study the role of single effectors in persistence, the ability of bacteria to survive in the host weeks after infection, revealed that both SspH1 and SspH2 significantly contributed to persistence of S. enterica serovar Typhimurium during systemic infection [ 194 ]. Studies carried out at the cellular level suggested that heterologous expression of SlrP in human epithelial HeLa cells induced defects in migration and adhesion [ 195 ] and increased cell death [ 105 ]. Additionally, using HeLa cells as infection model, SspH1 was shown, together with SptP, to downregulate the NF-κB-dependent expression of the pro-inflammatory cytokine IL-8 [ 137 ].…”
Section: E3 Ubiquitin Ligases Of the Nel Familymentioning
confidence: 99%
“…Salmonella effector proteins also induce apoptosis via these signaling pathways. SlrP is an E3 ubiquitin ligase translocated by both SPI-1 and SPI-2 that interacts with thioredoxin-1 (Trx1) and the ER chaperone protein, ERdj3 (4346). Expression of SlrP increased cytotoxicity in infected HeLa cells, suggesting a role for SlrP in inducing intrinsic apoptosis in infected epithelial cells (43, 44).…”
Section: Apoptotic Cell Death Pathways During Salmonella Infectionmentioning
confidence: 99%
“…Thus, it is of fundamental importance to gain further understandings of the mechanisms operated by bacterial effectors in order to hijack host ubiquitylation pathways. For instance, among the still so many unanswered questions, identifying whether the mono-ubiquitylation of Salmonella SopB is performed by host or bacterial E3 ligases, or which E3 ligase is responsible for the apposition of K63-linked ubiquitin chains on the Salmonella outer membrane [ 103 ] and which pathogen effector targets remain to be identified [ 104 ], and could help developing novel anti-bacterial therapeutic strategies besides the common and well-established ones based on traditional antibiotics.…”
Section: Discussionmentioning
confidence: 99%